2020
DOI: 10.1093/database/baz159
|View full text |Cite
|
Sign up to set email alerts
|

NipahVR: a resource of multi-targeted putative therapeutics and epitopes for the Nipah virus

Abstract: Nipah virus (NiV) is an emerging and priority pathogen from the Paramyxoviridae family with a high fatality rate. It causes various diseases such as respiratory ailments and encephalitis and poses a great threat to humans and livestock. Despite various efforts, there is no approved antiviral treatment available. Therefore, to expedite and assist the research, we have developed an integrative resource NipahVR (http://bioinfo.imtech.res.in/manojk/nipahvr/) for the multi-targeted putative therapeutics and epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…AEFFSFFRTF, IPFLFLSAY, ETDDYNGIY, SQNLLVTSY) show a match with previous studies[35][36][37][38], indicating consensus of epitope screening by different approaches and methods (Supplementary table…”
supporting
confidence: 83%
See 1 more Smart Citation
“…AEFFSFFRTF, IPFLFLSAY, ETDDYNGIY, SQNLLVTSY) show a match with previous studies[35][36][37][38], indicating consensus of epitope screening by different approaches and methods (Supplementary table…”
supporting
confidence: 83%
“…Along with the B cell, the T cell also play a critical role in immune response against NiV infection. In recent studies a number of B cell and T cell epitopes from the NIPAH proteome have been reported [27][28][29][30][31][32][33][34][35][36][37][38]. Further different approaches were proposed for the design of multi epitope vaccines [39,44].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the drugs designed for multiple protein targets are extensively preferable for the treatment of infectious, inherited and complex diseases due to low treatment cost, less drug dosage and minimal side effect and drug–drug interactions. Therefore, with the immediate requirement of multi-targeted strategies against the novel coronavirus SARS-CoV-2, with either biologically active drug-like molecules or approved drugs are in pressing priority [ 6 , 24 , 25 ]. Recent advancements in the computational techniques have proven their efficiency for identifying the potential drug candidates [ 7 , 26–28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The world is currently undergoing and living with the great threat of pathogenic severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which has newly emerged from Wuhan, Hubei province, China ( Du Toit, 2020 ; Hui et al, 2020 ; Wang C. et al, 2020 ). Apart from this, in recent years, we have also witnessed sporadic outbreaks and epidemics of various lethal viruses, i.e., Ebola, Zika, Nipah, etc ( Gupta et al, 2016 , 2020 ). The current pandemic of SARS-CoV-2 (also named as 2019-nCoV) is now reported to spread over 199 countries and to be responsible for excessive economic loss worldwide ( Zhang and Liu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%